2014
DOI: 10.2174/1568026614666140826120716
|View full text |Cite
|
Sign up to set email alerts
|

Positive Allosteric Modulators for mGluR2 Receptors: A Medicinal Chemistry Perspective

Abstract: This review summarizes drug discovery efforts on mGluR2 positive allosteric modulators IntroductionGlutamate is the major excitatory neurotransmitter that plays a role in eliciting and modulating synaptic responses. These processes involve ionotropic (AMPA, NMDA, kainate) and metabotropic receptors. Up to now eight metabotropic glutamate (mGluR) receptors have been described and characterized [1] and were classified into three subgroups based on their similarity in sequence, signaling and pharmacology [2]. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The benzyl substituted benzotriazole derivative 4 was identified from this campaign as an attractive small molecule with low micromolar activity (mGluR2 PAM EC 50 = 3 μM, Figure 2). These data confirmed that 4 is a much smaller (N hev = 16) but still potent compound with higher ligand efficiency (LE = 0.49) as compared to known mGluR2 PAMs 12 (average N hev = 29 ± 4; average LE = 0.25 ± 0.4) that validates it for follow-up studies. Freedom to operate analysis identified only a 5-disubstituted benzotriazole series of Merck 17−19 that was subjected to detailed evaluation.…”
Section: ■ Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The benzyl substituted benzotriazole derivative 4 was identified from this campaign as an attractive small molecule with low micromolar activity (mGluR2 PAM EC 50 = 3 μM, Figure 2). These data confirmed that 4 is a much smaller (N hev = 16) but still potent compound with higher ligand efficiency (LE = 0.49) as compared to known mGluR2 PAMs 12 (average N hev = 29 ± 4; average LE = 0.25 ± 0.4) that validates it for follow-up studies. Freedom to operate analysis identified only a 5-disubstituted benzotriazole series of Merck 17−19 that was subjected to detailed evaluation.…”
Section: ■ Introductionsupporting
confidence: 69%
“…Over the past decade a large number of structurally different chemotypes have been disclosed and reviewed . To date, two mGluR2 PAM molecules have reached the clinic (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that allosteric modulators bind at an alternative site to orthosteric agonists offers multiple potential benefits: opportunity to access a novel chemical space, potential for improved selectivity versus other members of the mGlu family, and lower potential for receptor desensitization and tolerance because PAMs function only in the presence of physiologically controlled levels of glutamate. To date, multiple series of selective mGlu2 receptor PAMs have been described, and two of them have entered the clinic: 7-methyl-5-[3-(piperazin-1-ylmethyl)-1,2,4-oxadiazol-5-yl]-2-[[4-(trifluoromethoxy)­phenyl]­methyl]-3 H -isoindol-1-one ( 4 , AZD8529) from AstraZeneca and 1-butyl-3-chloro-4-(4-phenyl-1-piperidinyl)-(1 H )-pyridone ( 5 , JNJ-40411813, also known as ADX71149) from Janssen Pharmaceuticals, Inc. (Janssen) and Addex Therapeutics (Addex). Compound 4 (Figure ) advanced into phase II clinical trials in schizophrenic patients in 2009, but it was discontinued in early 2011 due to lack of efficacy .…”
Section: Introductionmentioning
confidence: 60%
“…A positive allosteric modulator (PAM) can increase the affinity and/or efficacy of the endogenous neurotransmitter glutamate binding to a site topologically distinct from the orthosteric (glutamate) ligand binding sites. PAMs of mGluR 2 have emerged as promising novel therapeutic agents for the treatment of several central nervous system (CNS) disorders. The mGluR 2 is expressed on presynaptic glutamatergic nerve terminals where it functions as an autoreceptor for glutamate. Thus, a mGlu 2 PAM can normalize excessive glutamatergic neurotransmission, which may be of benefit in disorders such as epilepsy , and schizophrenia. , …”
mentioning
confidence: 99%